Clinical pharmacologic aspects of immune checkpoint inhibitors in cancer therapy - Kim, Kyu-pyo; Jung, Hun (Translational and clinical pharmacology, 2016)
During the past two years, three immune checkpoint inhibitors, ipilimumab, nivolumab and pembrolizumab, have been approved and revolutionized cancer immunotherapy. Translational and clinical pharmacology of these agents have contributed in identifying patients who will receive benefit, dose effect relationship and surrogate endpoints of clinical benefit. In addition, population pharmacokinetics/pharmacodynamics have facilitated scientific clinical development, which has led to accelerated approval of these agents. This paradigm may show how early phase studies may allow identification of subgroup of patients who can benefit and subsequent approval of drugs based on smaller patient population. This may speed the access of effective treatment for patients with life-threatening diseases. KCI Citation Count: 0